2016
DOI: 10.1097/j.pain.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the transition from acute to persistent musculoskeletal pain in children and adolescents: a prospective study

Abstract: Strategies directed at the prevention of disabling pain have been suggested as a public health priority, making early identification of youth at risk for poor outcomes critical. At present limited information is available to predict which youth presenting with acute pain are at risk for persistence. The aims of this prospective longitudinal study were to identify biopsychosocial factors in the acute period that predict the transition to persistent pain in youth with new-onset musculoskeletal (MSK) pain complai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 47 publications
2
97
0
8
Order By: Relevance
“…Although speculative, parent ACEs may impact parents' health which could, in turn, increase children's risk of chronic pain through parent (eg, chronic pain) and child (eg, depressive symptoms) risk factors. 18 , 26 , 27 To the best of our knowledge, only 1 study has examined parent ACEs in the context of chronic pain. Dennis et al examined mothers with chronic pain and their children and found that maternal ACEs were not related to child pain but were indirectly related to child depressive symptoms through maternal depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although speculative, parent ACEs may impact parents' health which could, in turn, increase children's risk of chronic pain through parent (eg, chronic pain) and child (eg, depressive symptoms) risk factors. 18 , 26 , 27 To the best of our knowledge, only 1 study has examined parent ACEs in the context of chronic pain. Dennis et al examined mothers with chronic pain and their children and found that maternal ACEs were not related to child pain but were indirectly related to child depressive symptoms through maternal depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Whether significant and unwanted sprouting of sensory and sympathetic nerve fibres also occurs in patients with genetic disorders of the skeleton, has yet to be determined. However, if ectopic nerve sprouting in bone does occur in these conditions, it may provide insight into the mechanisms that drive the transition from acute to chronic skeletal pain in these patients .…”
Section: Ectopic Sprouting In Sensory and Sympathetic Nerve Fibresmentioning
confidence: 99%
“…Una reciente revisión sistemática (87) demostró que la depresión es un factor predictor del desarrollo de dolor crónico no oncológico en personas mayores de 18 años. De los estudios incluidos en esta revisión, el catastrofismo y la depresión fueron los factores cognitivo-afectivos más estudiados y que presentaron mayor correlación con el dolor musculoesquelético (25,27,28,31,37,38).…”
Section: Discussionunclassified
“…La relación entre el dolor y la depresión se ha estudiado bastante. Desde esta perspectiva se ha descubierto cierta relación lineal entre síntomas depresivos, discapacidad y dolor, la cual se traduce en una menor calidad de vida (37,38). La depresión ha sido identificada como un factor predictor de dolor crónico en muñecas, manos, hombros y columna cervical (39-41).…”
Section: Depresión Y Ansiedadunclassified